(3eUHGM GdCQhGMs - (3YHO Gddg Hf YeQ Hf eMeO Hf Ydj , GdTjQGRj GdHjVGhj, CHh SYjO CHh GdNjQ fGUQ GdOjf,J (B685 (3g` s ((3eMeO Hf KGHJ Hf SYjO GdhQjfdGfi s)
(3ChdgG (B:s
(3GdMeO ddg GdeJaQO HEjLGO cd ehLhO hEfTGFg hHYO aGYde Cfi LeYJ dc UahI cdGe GdChdjf hRHOI CbGhjd GdBNQjf ai Yde GUhd GdOjf , hSejJg HeUHGM GdCQhGM s
(3BNQgG (B:s
(3GdKGdKI jLH JYXje GdUMGHI Gddge habfG dSjQJge hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B110 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B298s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1704s
Keywords: (3CUhd Gdabgs